2022
DOI: 10.1111/mcn.13431
|View full text |Cite
|
Sign up to set email alerts
|

Anthropometric deficits and the associated risk of death by age and sex in children aged 6–59 months: A meta‐analysis

Abstract: Risk of death from undernutrition is thought to be higher in younger than in older children, but evidence is mixed. Research also demonstrates sex differences whereby boys have a higher prevalence of undernutrition than girls. This analysis described mortality risk associated with anthropometric deficits (wasting, underweight and stunting) in children 6-59 months by age and sex. We categorised children into younger (6-23 months) and older (24-59 months) age groups. Age and sex variations in near-term (within 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
1
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 30 publications
1
1
2
Order By: Relevance
“…The 2020 Global Nutrition Report also showed that boys under‐5 years of age had a higher prevalence of stunted and wasted compared to girls (Micha et al, 2020 ). However, contrary to our results, in a recent study, the risk of death was found to be similar in boys and girls (Thurstans et al, 2023 ). One possible explanation could be that their analysis was limited to children aged 6–59 months, while ours to infants aged <6 months.…”
Section: Discussioncontrasting
confidence: 99%
“…The 2020 Global Nutrition Report also showed that boys under‐5 years of age had a higher prevalence of stunted and wasted compared to girls (Micha et al, 2020 ). However, contrary to our results, in a recent study, the risk of death was found to be similar in boys and girls (Thurstans et al, 2023 ). One possible explanation could be that their analysis was limited to children aged 6–59 months, while ours to infants aged <6 months.…”
Section: Discussioncontrasting
confidence: 99%
“…Two recent metaanalyses provide support to the nutritional disadvantages in boys, one conducted in 84 countries among older children aged 6-59 months (Khara et al, 2018), and another conducted in 74 studies among children aged 0-59 months (Thurstans et al, 2020). However, contrary to our results, the risk of death was found to be similar in boys and girls (Thurstans et al, 2023). The 2020 Global Nutrition Report also showed that boys under-five years of age had a higher prevalence of stunted and wasted compared to girls (Micha et al, 2020).…”
Section: Discussioncontrasting
confidence: 99%
“…We did not observe any differences in age or sex in relation to mortality. While this sample likely lacked sufficient power for this outcome, the finding is consistent with our recent meta‐analysis (S. Thurstans et al, 2022 ), showing no difference in the risk of mortality associated with wasting between boys and girls and between children under 2 years versus those 2–5 years. This highlights the importance of access to treatment for all children under 5 years, regardless of age and sex.…”
Section: Discussionsupporting
confidence: 88%
“…Wasting has also been shown to peak in younger children between 0 and 3 months (Benjamin‐Chung et al, 2020; Mertens et al, 2023). Despite higher levels of wasting among children under 2 years compared with children aged 2–4 years (14% and 9%, respectively) (Karlsson et al, 2022), we recently demonstrated equivalent levels of associated mortality risk for younger (6–23 months) and older (24–59 months) wasted children and equivalent levels of mortality risk between wasted girls and boys (S. Thurstans et al, 2022).…”
Section: Introductionmentioning
confidence: 86%